2000
DOI: 10.2337/diacare.23.11.1642
|View full text |Cite
|
Sign up to set email alerts
|

Independent effects of peripheral nerve dysfunction on lower-extremity physical function in old age: the Women's Health and Aging Study.

Abstract: OBJECTIVE -To determine the role of peripheral nerve dysfunction (PND) in the disablement pathway.RESEARCH DESIGN AND METHODS -Vibration perception threshold (VPT) was measured in 894 women aged Ն65 years, and those with normal peripheral nerve function and with mild, moderate, and severe PND were identified. Lower-extremity impairments included quadriceps strength (kilograms) and three progressively difficult balance tasks (able/unable). Functional limitations included rising from a chair (able/unable) and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
1
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 28 publications
11
105
1
8
Order By: Relevance
“…Richardson and Hurvitz (28) identified peripheral neuropathy, measured as nerve conduction velocity, as a risk factor for falls. Studies in older adults with and without diabetes have found that peripheral neuropathy is associated with reduced balance and walking speed (29). We found that loss of pressure sensitivity was independently associated with falling.…”
Section: Multivariable Adjustmentmentioning
confidence: 48%
“…Richardson and Hurvitz (28) identified peripheral neuropathy, measured as nerve conduction velocity, as a risk factor for falls. Studies in older adults with and without diabetes have found that peripheral neuropathy is associated with reduced balance and walking speed (29). We found that loss of pressure sensitivity was independently associated with falling.…”
Section: Multivariable Adjustmentmentioning
confidence: 48%
“…Diabetic somatic peripheral neuropathy (DPN) is a chronic and potentially disabling complication of diabetes, having a negative impact on physical and psychosocial functioning and on the quality of life of persons affected by this disorder [1][2][3][4]. DPN is not a single entity but encompasses a variety of clinical manifestations that can include unremitting pain, reduced feeling in the feet and postural instability.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in measuring vibrotactile sensitivity using objective methods is growing due to a proposed association with functional mobility in older adults [31] and also in connection with clinical studies testing the effectiveness of interventions aimed at improving peripheral nerve function especially in diabetic patients [36]. Accordingly, commercial devices have been developed that assess vibration sensitivity through psychophysical techniques aimed at identifying the minimum amplitude of vibratory stimulus required for perception (VPT).…”
Section: Introductionmentioning
confidence: 99%